Characteristic analysis and direct measurement for air gap magnetic field of external rotor permanent magnet synchronous motors in electric vehicles. Issue 10 (4th August 2020) - Ma, Conggan; Zhou, Shengsen; Yang, Na; Degano, Michele; Gerada, Christopher; Fang, Jianguang; Liu, Qinghe
Abstract : In this study, the air gap magnetic field characteristics of external rotor permanent magnet synchronous motors (PMSMs) under both the stator and rotor coordinate systems considering low‐order current harmonics and high‐order sideband current harmonics are analysed. A direct measurement technique (DMT) for air‐gap magnetic field is proposed. First, an analytical model of air gap magnetic field of external rotor PMSMs is established. The spatial order and frequency characteristics of stator/rotor air gap magnetic field are revealed. Then, a 24‐pole 27‐slot external rotor PMSM is taken as an example. The analytical and finite element (FE) results are compared and analysed. The difference of the spatial order and frequency characteristics between the stator and rotor air gap magnetic field are verified. Next, a new DMT is proposed, which can detect the precise distribution and local microscopic characteristics on the order of 10 −1 mm with high resolution. The accuracy of analytical and FE model are verified by the DMT and an indirect experimental test of no‐load back electromotive force. Finally, the mechanical challenges of in‐wheel motors and the practicablility of DMT for eccentricity detection are further discussed.